Genetically predicted serum ferritin mediates the association between inflammatory cytokines and non-alcoholic fatty liver disease - Liu, XiaoQian; Jin, JianHong; Wang, BaoFa; Ge, LinPu (Frontiers in Endocrinology, 2024)
Objective: Investigating the causal relationship between inflammatory cytokines and Non-al coholic fatty liver disease(NAFLD) and identifying and quantifying the role of serum ferrit in as a potential mediator.Methods: Genetic summary statistics were derived from open genome-wide association study (GWAS) databases. We conducted a two-sample Mendelian randomization (MR) analysis to investigate the relationship between inflammatory cytokines (8,293 individuals ) and NAFLD (8,434 cases, 770,180 controls). Furthermore, we used two-step MR to quantitate the proportion of the effect of serum ferritin-mediated inflammatory cytokines on NAFLD. In this study, we primarily utilized inverse-variance-weighted Mendelian randomization (MR-IVW) and reverse MR analysis methods, while other methods were also performed for sensitivity analysis ， false discovery rate (FDR) <0.0012 as statistical significance in MR analyses.Our results indicated that high levels of Eotaxin, regulated upon activation norma l T cell expressed and presumably secreted(RANTES), Interleukin-2(IL-2), macrophage mig ration inhibitory factor(MIF), tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and Stem cell factor(SCF) were associated with increased risks of NAFLD, while high C utaneous T cell-attracting chemokine(CTACK) and Interleukin-16(IL-16) levels that reduced the risk of NAFLD.The proportion of genetically predicted NAFLD mediated by ferritin was 2.1%(95% CI = 1.39%-5.61%).In conclusion, our study identified a causal relationship between inflammatory cytokines and NAFLD, with a small proportion of the effect mediated by ferritin, but a majority of the effect of inflammatory cytokines on NAFLD remains unclear. Further resea rch is needed on additional risk factors as potential mediators.